Post-harvest cultivation with seafood process waters improves protein levels of Ulva fenestrata while retaining important food sensory attributes - Stedt, Kristoffer; Steinhagen, Sophie; Trigo, João P.; Kollander, Barbro; Undeland, Ingrid; Toth, Gunilla B.; Wendin, Karin; Pavia, Henrik (Frontiers in Marine Science, 2022)
Seaweed aquaculture can provide the growing human population with a sustainable source of proteins. Sea-based cultivation is an effective method for farming seaweeds on a large scale and can yield high biomass output. However, the quality and biochemical composition of the biomass is seasonally dependent, which limits the harvests to certain periods of the year. Here we show the possibility to extend the sea-based cultivation season of Ulva fenestrata when aiming for high protein levels, by post-harvest treatment in herring production process waters. We harvested U. fenestrata at an optimal period in terms of yield, but suboptimal in terms of protein content. We then cultivated the seaweed in onshore tank systems with the nutrient-rich process waters for 14 days. We monitored biomass yield, crude protein content, amino acid composition, and content of the health concerning metals arsenic, mercury, lead, and cadmium, as well as the sensory properties of the dried biomass. After cultivation in the process waters, biomass yields were 30 - 40% higher (210 – 230 g fresh weight) compared to in seawater (160 g fresh weight). Also, the crude protein and amino acid content increased three to five times in the process waters, reaching 12 - 17 and 15 – 21% dry weight, respectively. The protein enriched biomass followed food graded standards for heavy metal content, and consumption of the biomass does not exceed health based reference points. Additionally, no sensory attributes regarded as negative were found. This rapid, post-harvest treatment can help extend the cultivation season of sea-based seaweed farms, maximizing their output of sustainable proteins.